METODE BELAJAR ONLINE TERHADAP TINGKAT KECERDASAN ANAK SD ERA PADEMI COVID-19 - Syafitri, Lili; Asmawati; Hendarmin, Rum; Hartati, Lesi (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2021)
In online learning, the teaching and learning process is facilitated by the use of the internet and digital media to convey the material. Online learning is believed to be more aligned with the current generation of students, who are well-known for their high level of integration with technology products. This is a form of digitization in the field of education that provides a number of advantages. From a practical standpoint, the benefits of online learning in the Covid-19 pandemic era include the ability for teachers and students to interact more effectively because they will not have to physically meet. Additionally, there is no classroom for formal education. The teaching and learning process can occur anyplace as long as the environment is conducive and can aid in concentration. Furthermore, there is no requirement to "dress well" or "look officially" to make it more flexible. A more appropriate approach to online learning is to take a technology strategy that is more appropriate for today's students than traditional classroom approaches. Besides that, the delivery methods employed in online learning programs are typically a blend of formal and informal. The Covid-19 pandemic has created numerous educational opportunities. Online education has separated classroom resources, such as teachers' markers and blackboards, and students' notes and pens. Students will receive more engaging instruction when they are exposed to a variety of media types, including photographs, videos, and audio. This community service is conducted at an elementary school in Jalan pembangunan Pakjo, specifically in Pakjo Elementary School of 126th, in order to facilitate MBKM between universities and elementary schools.